Social network characteristics, perceived drinking norms and hazardous alcohol use (2012)
Efforts by researchers, policy makers and other stakeholders to bring about significant reductions in alcohol use among the youth appears not to be yielding desired results, as the problem of hazardous drinking among the youth has persisted. One possible problem is that studies and policies on alcohol have not adequately situated the problem within relevant social contexts. This cross-sectional study examined the influence of social network characteristics, perceived drinking norms and demographic variables on hazardous drinking among 1,315 adult males newly recruited into a youth empowerment scheme in a state in Southwest Nigeria. Data were collected using structured questionnaire. Results showed that about 18% of the respondents reported scores falling within the hazardous drinking zones while 13% were abstainers. Hierarchical multiple regression analyses were performed to explore the extent to which each of the network characteristics and other factors predicted hazardous drinking. Age (β = -19; p<.05) and educational status (β = -16; p<.05) of participants significantly predicted hazardous drinking by accounting for about 15% of the explained variance in hazardous drinking. Social network characteristics accounted for about 33% of the explained variance in hazardous drinking. The importance of these and other findings of the study, and the need to factor in normative and social influences in alcohol-reduction intervention programmes were highlighted.